Modeling and Forecasting Volatility of Qatar Stock Exchange in light of the blockade and Covid-19 crises Using GARCH Models - Derbal Amina; Abdel Malek Lakhdar; Souar Youcef (Journal of North African Economies, 2025)
This study aims to model the Volatility of the (Qatar Stock Exchange) QSE returns and to forecast them out of the sample using GARCH models using the database of daily closing prices for the QSE index during the period (04/01/2016-07/07/2022). The study concludes that the GARCH model (1,1) is the best model for estimating and forecasting the volatility in the returns of the QSE index out of sample. It is also found that the returns will take stable levels in the short term . despite the critical economic situation and health instability as far as the region and the whole World. From here, we conclude that the blockade crisis prepared Qatar for the COVID-19 crisis, and the COVID-19 crisis prepared Qatar for future crises. Through excellence in various political, economic, financial and social fields.